Time management from an Islamic perspective: an exploratory study - Islam, Rafikul; Rahman, Mizanur; Wahra, Ali M. (World Academy of Islamic Management, 2022)
Studies on Time Management from the conventional perspective have been a vibrant research area since 1990s. However, not much work has been done on Time Management from an Islamic perspective despite the fact that managing time in Islam is taught to be of paramount importance in life. Many Qur’anic verses as well as hadiths deal with time and emphasize on the importance of time management. The purpose of this study, which is an exploratory one, is to develop some guidelines on how to utilize time as epitomized from the Islamic teachings. The study is quantitative in nature wherein analysis is done on data collected from 150 respondents through self-administered questionnaires survey. The SPSS version 25 was used to analyze the collected data. Consequently, results reveal two main findings namely identification of two sets of activities whereby the first set pertains to those which Muslims should be spending more time on them. The second set is time-waster activities that Muslims should avoid. Limitations and possible future works are also suggested at the end of the paper. Hence, this study highlights that Time Management in an Islamic perspective is all about managing time fruitfully and meaningfully in order to reap Allah’s blessings.